2008
DOI: 10.3139/146.101742
|View full text |Cite
|
Sign up to set email alerts
|

Thermal, mechanical and fretting fatigue of silicon nitride

Abstract: Tools for hot wire rolling are exposed to high thermal, mechanical and tribological loadings during service. Ceramic materials such as silicon nitride possess good mechanical and tribological properties up to temperatures where most of today' roller materials do not exhibit acceptable reliability. In the present paper basic mechanical properties under thermal and mechanical loading as well as the damage behaviour of Si3N4 have been investigated in high cycle thermal fatigue and dynamic as well as cyclic four p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 5 publications
1
9
0
Order By: Relevance
“…These findings confirmed the results presented in Lengauer et al (2005). Additionally, in the work of Schwind et al (2008), it was suggested that cyclic temperature loading did not reveal clear fatigue effects on the tested silicon nitride material. On the other hand, it was experimentally established in Kailer (2009) that tribochemical effects are accelerated at high rolling temperatures, and that these effects have a desirable influence on the silicon nitride rolls.…”
Section: Introductionsupporting
confidence: 93%
See 1 more Smart Citation
“…These findings confirmed the results presented in Lengauer et al (2005). Additionally, in the work of Schwind et al (2008), it was suggested that cyclic temperature loading did not reveal clear fatigue effects on the tested silicon nitride material. On the other hand, it was experimentally established in Kailer (2009) that tribochemical effects are accelerated at high rolling temperatures, and that these effects have a desirable influence on the silicon nitride rolls.…”
Section: Introductionsupporting
confidence: 93%
“…When rolling steel 1.4310L, the FE-simulations predicted tensile stresses well below the four-point bending strength of SL 200 BG (1021 MPa at RT) (Schwind et al, 2008). These moderate tensile stresses explain the fatigue induced damage observed in the experiments.…”
Section: Discussionmentioning
confidence: 92%
“…Also, it is important recognize that the fatigue behavior of silicon nitride and similar ceramics can be sensitive to different environmental factors such as humidity, elevated temperatures, and exposure to liquids . Such exposure can give accelerated crack growth over what would otherwise be expected based on data from ambient conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Fatigue life testing of smooth silicon nitride specimens reveals inherent scatter due to the fatigue life being highly sensitive to variations in the initial flaw size . Predicting a fatigue strength or lifetime distribution from a flaw size distribution can be done in a straightforward manner using Weibull parameters and fracture mechanics when the concept of similitude is assumed to be valid .…”
Section: Introductionmentioning
confidence: 99%
“…The material considered in this study is a commercial silicon nitride (Si 3 N 4 ‐SL200 from Ceramtec, Germany) with 3 wt% Al 2 O 3 and 3 wt% Y 2 O 3 . Inert strength tests and cyclic lifetime tests were conducted on standard four‐point‐bending specimens in ambient air in a previous study . Cyclic tests were run at 60 Hz for the two load ratios R = P min / P max = 0.1 and R = 0.5 and tests were terminated if a specimen had not failed after 10 7 cycles (run out specimen).…”
Section: Methodsmentioning
confidence: 99%